Students' Concept Mastery: Reasoning Ability and Concept Mastery of Evolution - Helmi; Nuryani Yogipratama Rustaman; Fransisca Sudarto Tapilouw; Topik Hidayat (Universitas Djuanda, 2019)
Now a days, students tend to learn the concept of evolution through various sources independently through memorizing or reading on their own and unaware of the mutual relations among them in everyday life. The tendency leads makes learning the concept of evolution becomes meaningless and not profound, even though there are many studies that states that scientific reasoning will make the knowledge gained more meaningful and profound. This study aims to test the hypothesis, is there whether any correlation between students' concept mastery levelwith students' scientific reasoning skills in the evolution learning process. A total of 33 students participated in this study. Students' reasoning skills are obtained through the use of Test of logical thinking (TOLT), while students' concept mastery of evolution was assessed using concept knowledge assessment. The results of this study indicate that there is a correlation between students' scientific reasoning skills and students' concept mastery, where the tendency is that students who think formally are more dominant in obtaining high scores or better concept mastery of the knowledge.